The proximal femoral bone geometry in plain radiographs - Grevenstein, David; Vidovic, Boris; Baltin, Christoph; Eysel, Peer; Spies, Christian; Unglaub, Frank; Oppermann, Johannes (Archives of Bone and Joint Surgery, 2020)
Background: Osteoporosis represents the most common bone disease and has to be respected in planning total hip replacement, especially against the background of increasing uncemented total hip replacement. In this context, theradiographic geometry of the proximal femur got into focus and is controversially discussed.The aim of the presented study was to find any difference regarding known indices for proximal femur bone geometrybetween patients with high-grade osteoarthritis and patients suffering from a femoral neck fracture caused by lowimpact trauma.Methods: Retrospective matched-paired analysis of 100 plane pelvic radiographs from 50 patients who suffered fromhigh-grade hip osteoarthritis and 50 patients who suffered from femoral neck fracture was performed. Measurement ofCanal-Bone Ratio (CBR), Canal-Calcar Ratio (CCR), Mineral Cortical Index (MCI) and Canal Flare Index (CFI) wereperformed.Results: CBR was significantly higher in the fracture-group (0.45 +/- 0.06 vs. 0.41 +/- 0.08) (P-value= 0.008). Moreover,the femoral thickness 10 cm below the trochanter minor [F] was significantly higher in the osteoarthritis-group (34.68+/- 4.14 vs 32.11 +/- 3.43) (P-value 0.001).Conclusion: In conclusion, patients with a femoral neck fracture demonstrated a higher CBR, which indicates a poorerbone quality. In case of planning a THA, the CBR is an index which can easily be measured and can be seen as onedecision criterion in THA regarding fixation technique.Level of evidence: III
Gesehen am 18.06.2024